Comme’ une caus ale ou un adverbe de maniere.PNG - EL.Fakhri, Amel Mahdi (مجلة كلية الاداب, 2022)
Our problem here is to "comme" is a causal condition or a gerund. The word "comme" is a common word used both in written and spoken language and despite its frequent use, it is rarely noticed in terms of grammatical or semantic function. Our aim of this study is to focus on its situational functions in particular.In conclusion we found that the word "comme" can perform the function of the concomitance and descriptive function and that despite the prevalence of its use followed by another adverb or a conjunction, but that the traditional grammar books do not study or notice these functions.